Comparison of the Porosity Parameter in Sediments Obtained Using Traditional and Precision Methods (Cenomanian Deposits in Western Siberia, Russia) - Vitaliya Naumenko; Mikhail Zavatskij; Daniil Skudar (Qubahan Academic Journal)
The study focuses on porosity, an important parameter for calculating reserves. Traditionally, weight-based methods are used in calculation, which implies a simple approach to estimating hydrocarbon reserves. However, this study is based on the need to show that effective reserve assessment and hydrocarbon production planning require a combination of various methods supplemented by dynamic modeling. The Cenomanian deposit of the Yamburgskoe and Yubileynoe deposits in Western Siberia, Russia is the object of the study. A comparison is made based on the data obtained during the direct analysis using Preobrazhensky's method and microtomography of the core of the Cenomanian deposit. The study is carried out to evaluate the representativeness of various methods of measuring porosity and to investigate directly the reservoir of the Cenomanian deposit